The choice of pension and retirement systems when post-1960s baby boomers start to retire in China - Hualei Yang (China Finance and Economic Review, 2016)
Background: Around 2015, with the alternation of population generation, post-1960s baby boomers start to retire and post-1990s and 2000s baby busters successively enter into labor market in China, which has led to the decrease of working-age population, the increase of pension burden. Methods: We use dynamic programming method by improving the traditional OLG model. Results: This paper finds that a combination of immediately delayed retirement and accumulated pension system should be implemented if based on the goal of maximizing output, while a combination of undelayed retirement and accumulated pension system should be implemented if based on the goal of maximizing utility. Certainly, with using efficiency of elements unchanged, with the decrease of working-age population caused by the alternation of population generation, the increase of pension burden and the disappearance of capital dividend, a sharp decline of future economic growth cannot be changed no matter what kind of pension and retirement systems are implemented. Conclusions: In view of the substitutability of family utility and social output and synthesizing reform resistance, a combination of gradually delayed retirement and accumulative pension system should be implemented. At the same time, on the premise of stabilizing short-term economic situation, we should look for a new engine for economic development by system reform in the long run.
Keywords: 330; Retirement system; Pension policy; Post-1960s baby boomers; Social output and family utility